Multimodal Resources to Enrich Meaning Construction by EFL Teacher - Eka Apriani; Umu Arifatul Azizah; Ruly Morgana; Syafryadin Syafryadin (Journal of English Education and Teaching, 2021)
This study aimed at exploring qualitatively the types and the applicative principles of multimodal resources which were utilized in teaching English. Eight Indonesian English teachers having varied teaching experiences were engaged as the participants in this study. They were selected purposively in accordance with several considerations. Those were that they owned sufficient teaching experiences, and currently were graduate English students. This condition could guarantee that they owned adequate practice and familiarity to the issues, knowledge, and technical terms related to multimodality and multimodal resources so that they managed to provide the expected data. The information regarding the types of multimodal resources was obtained from questionnaire, and that about the applicative principles was explored through interview. This study found 12 types of multimodal resources utilized by the participants in that they ranged into: speech, body language or gesture, auditory elements, verbal expression, facial expression, music, writing, layout, graphics, pictures or photographs, animations or moving images, and videos. In addition this study also provided in details the data concerning with the applicative principles of multimodal resources. This study was essential because it could be one of required references for Indonesian English teachers to develop the meaningfulness of English instructions.